HEREDITARY AND EDUCATIONAL FACTORS IN THE DECISION TO OWN AN AGRICULTURAL BUSINESS - Vitriyani Tri Purwaningsih; Dian Fajarini; Resha Moniyana Putri; Aryan Danil Mirza. BR (TECHNOBIZ : International Journal of Business, 2022)
Many people in Indonesia make the decision to open a business, especially on small and medium scales. The decision to have a business is certainly motivated by various factors. Using household survey data from the fifth Indonesia Family Life Survey, this study aims to analyze the factors driving Indonesia’s household decisions to open an agricultural business. The data in this study is cross-section with the logistic regression method. The findings of this study indicate that a person's decision to open an agricultural business is strongly driven by hereditary factors from their parents and the length of education. Other factors influencing the decision to open an agricultural business are ethnicity, gender, marital status, age, and area of residence.